2013
DOI: 10.1109/jsen.2013.2238376
|View full text |Cite
|
Sign up to set email alerts
|

Cancellation of Unwanted Doppler Radar Sensor Motion Using Empirical Mode Decomposition

Abstract: The operation of microwave Doppler radar for sensing physiological motion signals is heavily compromised under sensor motion. To that end, we investigate the feasibility of applying empirical mode decomposition method in this context, and demonstrate its effectiveness in removing sensor motion artifacts. This method is shown to be effective in canceling unwanted sensor motion with precision sufficient to enable accurate heart rate extraction. Theoretical analysis and simulation results illustrate the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…Therefore, this expected value, which has second-order cylostationary characteristics according to (16), is interpreted as a statistical ensemble average [21]. □ We exemplify the above theorems using analysis and experimental results in the following section.…”
Section: Cyclostationary Statistical Model Of the Biomedical Return Smentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, this expected value, which has second-order cylostationary characteristics according to (16), is interpreted as a statistical ensemble average [21]. □ We exemplify the above theorems using analysis and experimental results in the following section.…”
Section: Cyclostationary Statistical Model Of the Biomedical Return Smentioning
confidence: 98%
“…As seen from (16), the SCF of the F y(t 1 )y * (t 2 ) (x 1 , x 2 ) ; lim signal will have all of its frequencies along the temporal frequency f-axis, because of the non-stationary nature of the signal, and discrete frequencies that correspond to hidden periodicities along the cycle frequency α-axis. According to (16), the spectral lines along the cyclic frequency axis have …”
Section: Second-order Cyclostationary Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Another method used to cancel RBM effect in vital signs acquisition is the radar implementation with self-injection locking [128]. In [129], the empirical mode decomposition (EMD) signal-processing technique was used to remove motion artifacts from the antenna and the subject. Another signal-processing method was used in [130] to remove the RBM effect on human vital signs.…”
Section: Challengesmentioning
confidence: 99%
“…Furthermore, signal processing techniques can be used to remove unwanted body movement in Doppler radars for vital signs detection. In [129], the empirical mode decomposition (EMD) technique was used to remove motion artifacts from the antenna and the subject. In [130] the authors demonstrated the possibility of measuring vital signs of humans by apply the cyclostatic transformation to Doppler radars in presence of RBM.…”
Section: Random Body Movement (Rbm) Cancellation Techniques In Dopplementioning
confidence: 99%